Case report: Rapid clinical improvement in acute exacerbation of MuSK-MG with efgartigimod - Zhu, Geke; Ma, Yongbo; Zhou, Han; Nie, Xiangtao; Qi, Wenjing; Hao, Lei; Guo, Xiuming (Frontiers in Immunology, 2024)
Myasthenia gravis with positive MuSK antibody often involves the bulbar muscles and is usually refractory to acetylcholinesterase inhibitors. For MuSK-MG patients who experience acute exacerbations and do not respond to conventional treatments, there is an urgent need to find more suitable treatment options. With the advent of biologic agents, efgartigimod has shown promising results in the treatment of MG. We report a 65-year-old MuSK-MG patient who presented with impaired eye movements initially, and the symptoms rapidly worsened within a week, affecting the limbs and neck muscles, and had difficulties in chewing and swallowing.Lymphoplasmapheresis did not achieve satisfactory results, but after a cycle of efgartigimod treatment, the patient's symptoms gradually improved and remained in a good clinical state for several months.